Experimental investigation of four-port MIMO-Dual-Band (MDB) antenna for n260/n263 mmWave bands with analysis including conformal & specific-absorption-rate - Manish Sharma; Tathababu Addepalli; Gaurav Sharma; Tanweer Ali (PLoS ONE, 2026)
The single-input-single-output (SISO) system or the single-port antenna faces the problem of path-loss and fading of the signals, which results in loss of data. However, the fast-data transmission is needed in an hour, and the multiple-input-multiple-output millimeter-Wave (MIMO mmWave ) technology satisfies the high-speed of communication without a low loss of data, irrespective of the design of the antenna. The millimeter-Wave bands need to be explored since the lower 5 G-sub 6 GHz is already overloaded with huge traffic and is unable to cater to the needs. Hence, to utilize millimeter-Wave bands for n260 and partial-n263 in FR2, a four-port MIMO mmWave antenna is designed. The proposed MIMO mmWave work is characterized for S-parameters, far-field results, bending analysis, and SAR calculation for on-body applications. This research article discusses ultra-compact dual-band MIMO mmWave antenna radiating EM Energy is designed for n260 and partial-n263 band with etched circular-patch printed on top-surface of 0.254 mm thickness Rogers-flexible substrate and ground on opposite surface. The single-port version occupies PCB space of 6 × 8 mm2 (0.93λ 0 ×1.23λ 0 ), and the four-port proposed version utilizes 12 × 16 mm 2 (1.85λ 0 ×2.47λ 0 ) space. The fabricated four-port mmWave antenna achieves impedance bandwidth of 36.60GHz-39.12GHz and 58.48GHz-61.48GHz. The MIMO antenna also offers an averaged gain in n260 and partial-n263 band corresponding to 6.532dBi & 6.978dBi. The conformal capability at 45° in the x-axis and y-axis maintains both the mmWave bands without much deviation in comparison with planar no-bending of the MIMO mmWave antenna. The diversity parameter for n260/ partial-n263 bands corresponds to Envelope Correlation Coefficient<2.78 × 10 -4 (38.0GHz)/2.93 × 10 -4 (60.0GHz), Diversity Gain mmWave ≈ 10.0dB (38.0GHz/60.0GHz), Total Active Reflection CoefficientmmWave < −7.358dB (38.0GHz)/-9.12dB (60.0GHz), Channel Capacity LossmmWave<1.58 × 10 -2 (38.0GHz)/1.83 × 10 -2 (60.0GHz) and Mean Effective Gain mmWave (all ports) ≈ -30.0dB (38.0GHz/60.0GHz) and is deployable in 5G infrastructure. The SAR analysis with respect to single port corresponds to 0.0174W/Kg at 38.0GHz and 0.0384W/Kg at 60.0W/Kg and the MIMOmmWave values are 0.00895W/Kg at 38.0GHz & 0.0301W/Kg at 60.0GHz.